eEF2K—a new target in breast cancers with combined inactivation of p53 and PTEN - Hege G Russnes; Carlos Caldas (EMBO Molecular Medicine)
Abstract Extensive efforts have now characterized the somatic molecular alterations in human breast cancer (Cancer Genome Atlas Network, 2012; Stephens et al, 2012) and have led to a re‐definition of the disease as a constellation of 10 distinct driver‐based subtypes (IntClust subtypes) (Curtis et al, 2012). The pursuit of druggable targets for each of these subtypes is now pressing. This is elegantly illustrated by the work of Liu et al (2014).